2016
DOI: 10.1063/1.4953820
|View full text |Cite
|
Sign up to set email alerts
|

Emitter/absorber interface of CdTe solar cells

Abstract: The performance of CdTe solar cells can be very sensitive to the emitter/absorber interface, especially for high-efficiency cells with high bulk lifetime. Performance losses from acceptor-type interface defects can be significant when interface defect states are located near mid-gap energies. Numerical simulations show that the emitter/absorber band alignment, the emitter doping and thickness, and the defect properties of the interface (i.e., defect density, defect type, and defect energy) can all play signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(107 citation statements)
references
References 26 publications
3
97
1
Order By: Relevance
“…This observation suggests that the dominant recombination for CdS buffered CBTS solar devices takes place at the heterojunction interface where holes from CBTS recombine with electrons from CdS, largely because of the conduction band misalignment and large lattice mismatch between CBTS and CdS. [13,30] As oxygenation increases, more CdSO 4 passivators form and the CBM of CdS:O shifts to higher energy as well. [9] In addition, the large lattice mismatch between CBTS and CdS may cause a high density of interface defects, which can act as effective paths for carrier recombination at the heterojunction interface.…”
Section: Figure 2amentioning
confidence: 99%
See 1 more Smart Citation
“…This observation suggests that the dominant recombination for CdS buffered CBTS solar devices takes place at the heterojunction interface where holes from CBTS recombine with electrons from CdS, largely because of the conduction band misalignment and large lattice mismatch between CBTS and CdS. [13,30] As oxygenation increases, more CdSO 4 passivators form and the CBM of CdS:O shifts to higher energy as well. [9] In addition, the large lattice mismatch between CBTS and CdS may cause a high density of interface defects, which can act as effective paths for carrier recombination at the heterojunction interface.…”
Section: Figure 2amentioning
confidence: 99%
“…[18] Therefore, the electron transport paths from CBTS are gradually reduced in CdS:O with the increase of oxygenation due to the formation of insulating CdSO 4 as illustrated in Figure 4f. This large conduction band offset, CBO = +0.56 V, can act as a robust barrier for the electron transport from the CBTS to the front contact, [13,30,31] even with the advantage of reducing interface recombination. Eventually, the increased R S 's dramatically degrade the FF's.…”
Section: Figure 2amentioning
confidence: 99%
“…A recent advance in CdTe solar cells is the replacement of the traditional CdS buffer (emitter) by a wide bandgap metal oxide, such as ZnMgO (ZMO) . This replacement not only avoids the current loss caused by CdS but also introduces a spike to the conduction band offset (CBO) between the buffer and CdTe absorber . Device modeling has shown that an appropriate CBO spike can reduce interface recombination and increase the open‐circuit voltages (V OC ) of CdTe solar cells .…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the hole barrier levels for CdTe/ZnSe heterojunction depends on both the valence band levels and the Fermi levels of the CdTe and ZnSe. A small positive conduction-band offset may help maintain good cell efficiency as it created a large hole barrier adjacent to the interface and reduced interface recombination [32][33][34]. Efficiency up to 11% has been attained in the case of Cu(In,Ga)Se 2 thin-film solar cells with ZnSe buffer layer [35] while >21% efficiency has been achieved for the ZnS buffer layer [36].…”
Section: Resultsmentioning
confidence: 99%